Scavengers : a novel - Boland, Kathleen (Novelist) (Viking, 2026)
"A cautious daughter and her eccentric, estranged mother set off into the Wild West in search of buried treasure - and a way back to each other - before they run out of patience, money, and options. Junior commodities analyst Bea Macon prizes security and control over adventure - especially after being raised by free spirit Christy, who has recently been living in Utah on Bea's dime. But when Bea is fired from her job after taking an uncharacteristic risk that backfires spectacularly, she books a one-way flight to Salt Lake City, where she plans to lay low and regroup before returning to Wall Street. Though she's not about to tell Christy exactly what happened back east, Bea quickly realizes that she isn't the only one keeping secrets: Christy has a man. She has a map. She has . . . a username on a forum devoted to unearthing $1 million in buried treasure that an eccentric antiquities dealer claims to have hidden somewhere in the western U.S.? Bea is convinced this is just another one of her mother's wild larks, an elaborate way to refuse, as she has for Bea's entire life, to finally grow up. But Christy believes she's onto something - and she's not the only one. When Bea realizes Christy is planning to rendezvous in a rural town called Mercy with the man she's been obsessively trading theories with online, she refuses to let her go alone. Out in the desert that one woman believes to be a promised land, the other a wasteland, they find themselves barreling toward a more high-stakes, transformative escapade than either of them could have imagined. Populated with unforgettable characters and set against one of the world's most oddly enrapturing landscapes, Scavengers is a funny and heartbreaking novel about old injuries, new beginnings, and the lengths to which we'll go to find, escape, and reinvent ourselves"-- Provided by publisher.